The art of paper Quilling = / 종이감기 공예 - 최선옥 (서울: 디자인소호, 2006)
An exquisite paper art book featuring quilling techniques for cards and gifts. With a focus on simple, elegant projects, The Art of Paper Quilling offers paper crafters a complete technique guide along with step-by-step project ideas for making beautiful framed pieces, cards, gifts, and more. The designs are all built upon simple rolled coils of paper that when grouped together, form intricate flowers, graceful butterflies, and delicate scrollwork. Quilled designs can be framed or used to embellish greeting cards, books and journals, and many types of simple paper structures. Claire Sun-ok Choi is an expert paper artist who has influenced the revival of this fanciful art form with her inspiring exhibits and internationally known books.
Dibujo a color.
Keywords: Trabajos en papel; 종이감기 -- 공예 -- El arte del papel -- QUILLING; Técnicas de quilling